HUMANOID ROBOT LOCALIZATION AND PATH PLANNING USING LOOKUP TABLE AND A-STAR ALGORITHM - Kusuma, Mario
Humanoid robot is the robot that build with human like structure. Humanoid robot in this research have a mission as a personal assistant to help the user to get a commanded object. As a personal assistant, humanoid robot needs to be equipped by the ability to navigate in indoor environment. Satellite navigation was not applicable for indoor environment, then the ultrasonic sensor and lookup table method are being used to estimate the robot position. Lookup table method was used to compare actual sensor reading from four ultrasonic sensor and a compass sensor. The output of the lookup table was robot coordinate in x-y axis cartesian coordinate. To reach the object position as commanded, a step by step path planning was needed for humanoid robot from start node to destination node. A-star was the algorithm which have been used to plan the optimal path in the miniature of the house. Automatic rerouting feature helps the robot when the robot moved to arbitrary node or when the robot missed the coordinate in waypoints. Robot ability to receive the command from user and moved from source node to destination node is the goal in this research. The experiment result from this research shows that the robot was able to follow the waypoint given from A-star algorithm output. The addition of auto rerouting helps the robot to find alternative path when the robot cannot reach the waypoint coordinate after thirty seconds.The average trip time from current coordinate to next coordinate beside the robot was 22 seconds, so the wait time of 30 seconds to rerouting is enough.